Proposed guidelines for the creation of an updated records management program for Valenzuela Medical Center (VMC) - Ladrera, Maribel R.; Buenrostro-Cabbab, Iyra S.; Lagrama, Eimee Rhea, C. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2014)
The focus of this study is the management of medical records from creation to disposition. Having a Records Management Program is a valuable tool that will serve as a guide for the effective and efficient management of medical records. The Valenzuela Medical Center (VMC) is the main subject of this study. Leading hospitals in the Philippines were also included such as the Medical City (TMC) and St. Luke's Medical Center (SLM|C) as benchmark hospitals.
The research is qualitative in nature to give an in-depth descriptive presentation of the findings of the study. The findings of the study revealed that the VMC is a compliant of DOH and ISO15489:2001. However, they need to create a Vital Records Program and Disaster Prevention Program for the Medical Records Department. Vital Records Program includes protection, preservation and management of the vital documents. On the other hand, Disaster Prevention Program includes disaster control and recovery planning. The VMC followed the DOH Medical Hospital Records Manual as a guide in the management of their records. The information gathered from the two benchmark hospitals, TMC and SLMC were used to identify the strengths and weaknesses of the VMC. Findings revealed that VMC is doing the same procedures done by the benchmark hospitals but as of now they do not have modern equipment and facilities for the improvement of their processes. Since VMC is a government hospital, they do not have enough budget to purchase those equipment and facilities.
The result of this study shows that the main problem encountered by the Records Department is the difficult attitude of the customer. Another aspect is having a multiple Patient Identification Number (PIN). PIN is a permanent number of patient all throughout his life whenever he will be admitted at that hospital. The problem arises when the patient is unconscious and unable to give his personal data. The encoder created another entry if he did not find any match.
The researcher find out that the strengths of the VMC are the leadership qualities of the records manager, having a Quality Management System, and Valenzuela government is very supportive to their needs. On the other hand, VMC's weaknesses is having a contractual staff, lack of modern equipment such as high tech scanners, high end computers, vaults and foam extinguishers that can help them to improve their services and at the same time protect their documents.
Due to complexity of handling medical records, medical records department must have a guide on the policies and procedures in their department. So, the most important factor in the management of medical records is to have an updated Records Management Program. The researcher recommended a guideline for creating an updated Records Management Program for VMC (see appendix E).
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Medical records -- Management -- Philippines; Records -- Management